Black feminism interpretation in Maya Angelo's poems with figurative language and imaginary analysis - Heni Alghaniy Maulidina (LPPM UNY, 2021)
Poetry is one type of literary work that has characteristics and characteristics makes it different from other literary works. Currently there are many poems written using the experience of discrimination as an object due to various conditions appearing in society. Besides that, there are also many female poets who writing poetry using a feminist approach. The purpose of this study is to identify the types of figurative language and images related to Maya Angelou in black feminism in her poetry. It also analyzes the influence of Maya Angelou's black feminist thought reflected in her poetry through figurative words and images. In this qualitative study, the authors use a descriptive method through several steps, preparation, data collection, and data analysis. The focus of this research is the analysis of figurative language, types of images, and black feminism in Maya Angelo's poems. The figurative language and imagination used in the poems are diverse, such as metaphor, personification, paradox, symbol, irony, irony, visual imagery, and auditory imagery. In this analysis it can be concluded that black feminism movement are courageous, brave and outspoken.Keywords: Black Feminism, Figurative Language, Imaginary, Maya Angelou, Poems